The Use of Transperineal Sector Biopsy as A First-Line Biopsy Strategy: A Multi-Institutional Analysis of Clinical Outcomes and Complications - Eldred-Evans, David; Kasivisvanathan, Veeru; Khan, Fahd; Hemelrijck, Mieke Van; Polson, Alexander; Acher, Peter; Popert, Richard (Urology Journal, 2016)
Purpose: Systematic transrectal ultrasound biopsies have been the first-line biopsy strategy in men with suspected prostate cancer for over 30 years. Transperineal biopsy is an alternative approach but has been predominately reserved as a repeat biopsy strategy and not widely used as a first-line approach. This study evaluates the diagnostic and clinical outcomes of transperineal sector biopsy (TPSB) as a first-line biopsy strategy in the diagnosis and management of prostate cancer. Materials and Methods: A multi-institutional review of 402 consecutive patients who underwent primary transperineal sector biopsy. All patients had no prior history of prostate biopsy. TPSB was carried out as a day-case procedure under general or regional anaesthesia. The cancer detection rate, location and complications for all cases were evaluated. Results: Prostate cancer was identified in 249 patients (61.9%) and was comparably sited across anterior, middle and posterior sectors. The disease was clinically significant (Gleason 3+4 or > 4mm maximum cancer length) in 187 patients (47%). Post biopsy urinary retention occurred in 6 patients (1.5%). Hematuria requiring overnight hospital admission occurred in 4 patients (1.0%). There were no cases of urosepsis. Conclusions: As a primary diagnostic strategy, TPSB is a safe and effective technique with high cancer detection rates. It also offers an attractive compromise to more extensive transperineal protocols, which can be more time-consuming and associated with higher morbidity.